Modeling of flood inundation for Zhabay river basin in Central Kazakhstan region - Baktybekov, K.S.; Aimbetov, A.; Rakhimzhanov, B.K.; Murat, A. (KU publ., 2020)
Frequency analysis is the estimation of how often a specified event will happen. This is the most important statistical technique in understanding the nature and magnitude of high discharge in a river. In this paper, the flood frequency of the Zhabay River Basin in the Central Kazakhstan Region is analyzed. The frequency analysis has been carried out using Gumbel’s distribution on based the eightyear flood data in the Zhabay River Basin which was provided by the hydrometeorological service “Kazhydromet”. The expected floods for various return periods (T) is obtained. Additionally, the digital terrain model for the Zhabay River Basin is presented. This model was provided by the first Kazakhstan Earth remote sensing satellite KazEOSat-1. The results of the research would be useful in forecasting floods in the Central Kazakhstan region.
Орталық Қазақстан аймағындағы Жабай өзенінің бассейнінде су тасқынын модельдеу.
Моделирование наводнения для бассейна реки Жабай в Центрально-Казахстанской области.
Keywords: modeling; floods; Zhabay River Basin; frequency analysis; Gumbel’s distribution; KazEOSat -1